2009
DOI: 10.1042/bst0371037
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of Rab6–effector complexes

Abstract: The small GTPase Rab6 regulates vesicle trafficking at the level of Golgi. Recently, the crystal structures of Rab6 in complexes with two unrelated effectors have been determined. The structure of Rab6a-GTP in complex with a 378-residue internal fragment of the effector Rab6IP1 (Rab6-interacting protein 1) has been solved. In addition, the structure of Rab6 with the golgin, GCC185, has also been determined. In both complexes, two alpha-helices from the effector mediate binding to switch I, switch II and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…In contrast, L723A, V727A, K730A, K730M, and L731A dramatically diminished association with Rab6 GTP , whereas R724A and L725A caused a partial, but statistically significant, reduction in binding. The requirement for leucine and valine residues in BicD for binding Rab6 is consistent with the well-established importance of interactions between hydrophobic features on Rab effectors with a hydrophobic triad within the G protein (Fernandes et al 2009). Figure 3D summarizes the findings from the mutagenesis experiments in the context of the BicD structure, with the side chain positions of residues important for Rab6 GTP binding shown in Supplemental Figure S6.…”
Section: Identification Of a Rab6supporting
confidence: 55%
“…In contrast, L723A, V727A, K730A, K730M, and L731A dramatically diminished association with Rab6 GTP , whereas R724A and L725A caused a partial, but statistically significant, reduction in binding. The requirement for leucine and valine residues in BicD for binding Rab6 is consistent with the well-established importance of interactions between hydrophobic features on Rab effectors with a hydrophobic triad within the G protein (Fernandes et al 2009). Figure 3D summarizes the findings from the mutagenesis experiments in the context of the BicD structure, with the side chain positions of residues important for Rab6 GTP binding shown in Supplemental Figure S6.…”
Section: Identification Of a Rab6supporting
confidence: 55%
“…Accessory proteins regulate Rab protein GTPase activity, nucleotide exchange and membrane binding to guide many Rab proteinprotein interactions [60]. Multiple Rabs are typically required for sequential transport steps along secretory pathways [55], with some Rabs being paradigmatic for trafficking at specific organelles, such as Rab5a on early endosomes, Rab11a on recycling endosomes, Rab7 on late endosomes and Rab6 on Golgi membranes: in this regard such Rabs are commonly used experimentally as organelle markers or to denote specific trafficking steps [61][62][63][64]. The functions of individual Rabs has largely been revealed through the experimental expression of GDP-or GTP-locked mutated proteins and through naturally occurring mutations that show up phenotypically as coat color variants in mice, due to defects in melanosome trafficking and melanin release.…”
Section: Rab Gtpase Proteinsmentioning
confidence: 99%
“…[There are two alternatively spliced forms -Rab6A and Rab6A′ -that might play different roles in trafficking in and out of the Golgi (Echard et al, 2000); hereafter, Rab6 refers to either the first of the isoforms or to the combination of the two.] In addition to its role in Golgi-to-ER retrograde transport, Rab6 has been involved in a number of other trafficking pathways to and from the Golgi (Grigoriev et al, 2007;Storrie et al, 2012;Mallard et al, 2002), and a large number of Rab6-interacting proteins have been identified, (Fernandes et al, 2009;Miserey-Lenkei et al, 2010;Lee et al, 2015;Kano et al, 2009). An exact definition of the different interactions involved in the multiple functions of Rab6 at the Golgi complex has not been attained yet (reviewed in Heffernan and Simpson, 2014).…”
Section: Lipid-dependent Sortingmentioning
confidence: 99%